Pemodelan Waktu Hilangnya Penglihatan Penderita Retinopati Diabetik dengan Beberapa Model Survival - Jonathan Ryan Wilianto; Ruhiyat; Hadi Sumarno (Limits: Journal of Mathematics and Its Applications, 2024)
Diabetic Retinopathy is a condition where blood vessels in the eye swell and leak due to too high blood sugar level. Patients can lose their eyesight because the leaked blood prevents light from reaching the retina. The Cox proportional hazard (CPH) model is a semiparametric survival model that can model the effect of covariates to the survival time. The consequence of the CPH model form is the assumption of proportional hazard, that is, the hazard function ratio of two given observations will be always the same over time. The frailty model can model the unobserved random effect that influences the survival time. Frailty is an unobserved risk factor that influences the survival of the observation. The Cox with frailty model is a combination of the CPH model and the frailty model. Significant covariates for the survival time of eyesight are the type of laser used, the risk group, and the eyeball operated on. By using the Gamma frailty, we obtain strong evidence that the frailty does affect the eyesight survival time. The Cox with frailty model can explain the survival time better than the CPH model. This can be seen from the fact that it has higher Akaike information criteria score than the CPH model.